An extension of q-zeta function - T. Kim; L. C. Jang; S. H. Rim (International Journal of Mathematics and Mathematical Sciences, 2004)
We will define the extension of q-Hurwitz zeta function due to Kim and Rim (2000) and study its properties. Finally, we lead to a useful new integral representation for the q-zeta function.